A synchronously chemically closed-loop and high-performance approach for furan-based copolyesters with robustness, high gas barriers, and high puncture resistance. Issue 21 (20th October 2022) - Li, Xing-Liang; Fu, Teng; Li, Zheng-Ming; Li, Yao; Wang, Xiu-Li; Wang, Yu-Zhong
Abstract : We propose a strategy for synchronously constructing chemical closed-loop and achieving high performance, enabled by the bio-based 2, 5-furandicarboxylic acid, 1, 4-butanediol and fossil-based by-product diethylene glycol. Abstract : Utilizing bio-based resources is an essential part of the sustainable development of plastics. Meanwhile, the end-of-life options of bio-based plastics must be considered to avoid contributing to the accumulation of plastic waste. To address the problem of end-of-life plastics and the trade-off between chemical closed-loop recycling and high performance, targeted selection of monomers and a method for the preparation of high-performance linear polyesters that can be rapidly closed-loop recycled without the addition of additional organic solvents under mild conditions are necessary. Herein, we report strategies for synchronously constructing chemical closed-loop polyesters and achieving high performance, by using linear furan-based poly(butylene furandicarboxylate-diethylene glycol) (PBD y F), synthesized from dimethyl 2, 5-furandicarboxylate, diethylene glycol (DEG) and 1, 4-butanediol (BDO). Adjusting the ratio of ethyleneoxyethylene and butylene groups can endow PBD y F with excellent tensile strength (77.8 MPa), puncture resistance properties (129.7 N mm −1 ), and barrier properties (CO2 0.0120 barrier and O2 0.0103 barrier) for PBD80 F. Processing can be performed by injection moulding, and additive manufacturing, such as 3D printing. Moreover, we developed a rapid chemical-solvolysis strategy under mild conditions without producing other organic waste by using DEG/BDO to obtain recycled 2, 5-furandicarboxylate, DEG, and BDO from PBDyF. Utilizing the differences in the solubility and boiling point, the recycled chemicals can be separated. The repolymerized polyester (rPBD y F) still maintains high performance compared with PBD y F. In our approach, the high-performance chemically recyclable copolyester, exhibiting greatly potential films or 3D printing applications, provides a state-of-the-art method for solving the trade-off problem between the chemical-recycling and high performance of previous linear polyesters, further supporting sustainable closed-loop chemistry.